Cardiac Troponins for the Diagnosis of Acute Myocardial Infarction in Chronic Kidney Disease. Issue 19 (2nd October 2018) - Kraus, Daniel; von Jeinsen, Beatrice; Tzikas, Stergios; Palapies, Lars; Zeller, Tanja; Bickel, Christoph; Fette, Georg; Lackner, Karl J.; Drechsler, Christiane; Neumann, Johannes T.; Baldus, Stephan; Blankenberg, Stefan; et al.
Abstract : Background: Patients with chronic kidney disease (CKD) are at high risk of myocardial infarction. Cardiac troponins are the biomarkers of choice for the diagnosis of acute myocardial infarction (AMI) without ST‐segment elevation (NSTE). In patients with CKD, troponin levels are often chronically elevated, which reduces their diagnostic utility when NSTE‐AMI is suspected. The aim of this study was to derive a diagnostic algorithm for serial troponin measurements in patients with CKD and suspected NSTE‐AMI. Methods and Results: Two cohorts, 1494 patients from a prospective cohort study with high‐sensitivity troponin I (hs‐cTnI) measurements and 7059 cases from a clinical registry with high‐sensitivity troponin T (hs‐cTnT ) measurements, were analyzed. The prospective cohort comprised 280 CKD patients (estimated glomerular filtration rate <60 mL/min/1.73 m 2 ). The registry data set contained 1581 CKD patients. In both cohorts, CKD patients were more likely to have adjudicated NSTE‐AMI than non‐CKD patients. The specificities of hs‐cTnI and hs‐cTnT to detect NSTE‐AMI were reduced with CKD (0.82 versus 0.91 for hs‐cTnI and 0.26 versus 0.73 for hs‐cTnT) but could be restored by applying optimized cutoffs to either the first or a second measurement after 3 hours. The best diagnostic performance was achieved with an algorithm that incorporates serial measurements and rules in or out AMI in 69% (hs‐cTnI) and 55% (hs‐cTnT) of CKD patients. Conclusions: The diagnostic performance of high‐sensitivity cardiac troponins in patients with CKD with suspected NSTE‐AMI is improved by use of an algorithm based on admission troponin and dynamic changes in troponin concentration.